Analisis Kepuasan Masyarakat Terhadap Pelayanan Publik di Kota Denpasar - Suryawan, Gede; Sukarsa, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 12, Desember 2015 (pp. 1445-1529), 2015)
The purpose of this study to identify factors that affect public services in the city of Denpasar and the implications of economic development strategies are applied by the Office of Integrated Services One Stop and Investment in Denpasar. The sample in this study amounted to175 respondents. Sampling using non-probability sampling with purposive approach to the side which is then processed using SPSS software by factor analysis techniques. The analysis result thata significant difference between Servqual factor to improving the quality of public service sin the city of Denpasar.Implications of economic development strategie sare applied only between the comfortable waiting rooms, wide parking space, toilet facilities were clean and officers dressed and clean
Keywords: quality of public services, tangibles, reability, responsivness, assurance, emphaty